Broadband ultrafast pulse generation with double wall carbon nanotubes - Hasan,T; Sun,Z; Popa,D; Kelleher,EJR; Bonaccorso,F; Flahaut,E; Torrisi,F; Trushkevych,O; Privitera,G; Nicolosi,V; Taylor,JR; Ferrari,AC (2011)
Materials with nonlinear optical properties are much sought after for ultrafast photonic applications. Mode-locked lasers can generate ultrafast pulses using saturable absorbers[1]. Currently, the dominant technology is based on semiconductor saturable absorber mirrors (SESAMs). However, narrow tuning range (tens of nm), complex fabrication and packaging limit their applications[2]. Single wall nanotubes (SWNTs) and graphene offer simpler and cost-effective solutions[1]. Broadband operation can be achieved in SWNTs using a distribution of tube diameters[1,3], or by using graphene[4-8], due to the gapless linear dispersion of Dirac electrons[8,9]. © 2011 IEEE.